Inside Asylum Bureaucracy: Organizing Refugee Status Determination in Austria - Dahlvik, Julia; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This open access monograph provides sociological insight into governmental action on the administration of asylum in the European context. It offers an in-depth understanding of how decision-making officials encounter and respond to structural contradictions in the asylum procedure produced by diverging legal, political, and administrative objectives. The study focuses on structural aspects on the one hand, such as legal and organisational elements, and aspects of agency on the other hand, examining the social practices and processes going on at the frontside and the backside of the administrative asylum system. Coverage is based on a case study using ethnographic methods, including qualitative interviews, participant observation, as well as artefact analysis. This case study is positioned within a broader context and allows for comparison within and beyond the European system, building a bridge to the international scientific community. In addition, the author links the empirical findings to sociological theory. She explains the identified patterns of social practice in asylum administration along the theories of social practices, social construction and structuration. This helps to contribute to the often missing theoretical development in this particular field of research. Overall, this book provides a sociological contribution to a key issue in today's debate on immigration in Europe and beyond. It will appeal to researchers, policy makers, administrators, and practitioners as well as students and readers interested in immigration and asylum.
Foreword -- Acknowledgements -- Part I: Claiming asylum in the 21st century: an institutional perspective -- 1.Introduction -- 2.Determining refugee status in the European context: the legal and institutional framework -- Part II: Setting the scene: the context and circumstances of work at the Federal Asylum Office -- 3.The organization: structure, environment and socialization -- 4.The asylum interview as a magnifying glass for key issues: conflicting norms, power struggles, and actors$1 (Bstrategies -- 5.Regulation vs. room for maneuver -- 6.Definitiveness vs. uncertainty -- 7.The human individual vs. the faceless case -- 8.Responsibility vs. dissociation -- Part IV: Conclusion and prospects: theorizing public officials$1 (Bpractices and practical ways ahead -- 9.Practices in focus: the dilemmas that evoke them and the effects they have -- 10.Practical implications: how to deal with structural dilemmas? .s
Keywords: Emigration and immigration; Sociology; Human Migration; Sociology